Framework para desarrollo de sistemas inmersivos para entrenamiento de equipos (2017)
"This article's objective is to define a framework, to be able to create solutions for a problem of group training, with a given set of restrictions. This solution will be immersive for the users that will use it, and therefore it will use elements of Virtual Reality, Augmented reality or mixed reality among others. In addition this article will try to specify the design of the given solution and be able to answer the question : What implies to give an effective training? Therefore we will try to understand this concept as a base of development for the solutions." -- Tomado del Formato de Documento de Grado.